Alleviation of exercise-induced dehydration under hot conditions by glycerol hyperhydration - Nishijima, T.; Tashiro, H.; Kato, M.; Saito, T.; Omori, T.; Chang, H.; Ohiwa, N.; Sakairi, Y.; Soya, H. (International Journal of Sport & Health Science, 2007)
Ingestion of glycerol with a large volume of fluid causes hyperhydration, which has been shown to increase thermoregulatory capacity and improve exercise performance under hot conditions, but in some cases causes nausea and headaches. However, it is still uncertain what kind of hydration regimen would be effective in producing a greater hyperhydration state and whether glycerol hydration would affect mood. This study compared the hyperhydration effectiveness of different hydration regimens, then examined whether glycerol hyperhydration prior to exercise alleviates exercise-induced dehydration, improves exercise performance under hot conditions, and affects mood while hydrated. Both the Bolus-G regimen: ingesting a relatively high concentration of glycerol fluid at the beginning of the hydration phase, and the G regimen: ingesting a low concentration of glycerol fluid through hydration phase, caused significant increase in body weight and decrease total urine volume, but there was no significant differences between two regimens. Ninety minutes after glycerol or placebo hydration by the Bolus-G regimen, six healthy well-trained volunteers performed a 70-min cycling test. The decrease of body weight after exercise versus pre-hydration was significantly smaller in the glycerol trial (1.4% of body weight) than in the placebo trial (2.5%). There were no significant differences in exercise performance and mood measured by a two-dimensional mood scale during the hydration phase. These results suggest that hyperhydration by glycerol alleviates exercise-induced dehydration during exercise in a hot environment but with no changes in exercise performance and mood.